(untitled) (BIRDEM Medical Journal, 2019)
Background: Diabetes and its complications are major causes of morbidity and mortality throughout the world. It has been observedthatpatients who develop prolonged orcomplicated course of acute viral hepatitis (AVH) often have underlying diabetes.This study was designed to compare the outcome of AVH between type 2 diabetic and non-diabetic patients. Methods: This prospective observational studywas done in BIRDEM General Hospital from July 2011 to December 2013.A total of 60 patients suffering fromAVH admitted in Gastrointestinal, Hepatobiliary and Pancreatic Disorders (GHPD) Department were included. Of them 30 patients were diabetic (group A) and 30 patients were nondiabetic (group B). Patients’clinicaland biochemical parameters were evaluated during hospital stay. Results: Aetiology of AVH were hepatitis E (76.67%), hepatitis B (16.67%) and hepatitis A (6.67%). Among two groups(group A vs group B respectively); age in years (mean±SD) was 47.8±10.8 vs 30.7±11.0,gender distribution was (M/F) 18/12 vs 25/5; serum bilirubin (mean±SEM) 15.6±6.2 mg/dl vs9.8±5.5 mg/dl (p=0.001), serum ALT (mean±SEM) 735.5±92.2 iu/L vs 1491.3±189.0 iu/L, (p=0.01) and serum AST (mean±SEM) 567.9±66.9 iu/L vs 1024.8±209.2 iu/L (p=0.036). Mean duration of hospital stay in days was 17.9±8.2 vs 11.0±5.1(p<0.001) in group A and group B respectively. Sub-acute hepatic failure developed in 5(16.6%) cases of group A andonly 1(3.3%) case in group B. Three (10%) cases of group A developed acute pancreatitis who recovered with conservative treatment. No case of mortality was observed during the follow-up period. Conclusion: Complications of AVH in diabetic patients were more than non-diabetics. Rational and appropriatemanagement in diabetic patients may reduce the morbidity and mortality rate. Birdem Med J 2019; 9(1): 14-17